Intellectual Capital and Firms’ Performance Measures of Listed Non-Financial Companies in Nigeria: Array - Adegbayibi, Adesanmi Timothy (The Journal of Accounting and Management, 2021)
The prolonged neglect of intellectual capital by management of firms is a major challenge due to the paradigm shift towards knowledge economy where performance and competitive edge of firms are no longer primarily a matter of machines and tools but of brains and harnessing those brains. It is in view of this that this study investigated the effect of intellectual capital on perfo rmance measures of listed non-financial companies in Nigeria between year 2007 and 2017. The study adopted ex-post facto research design and data were obtained from secondary sources through the audited annual reports of sampled firms and the fact books of Nigerian Stock Exchange. Data such as human capital efficiency, structural capital efficiency and capital employed efficiency were proxies for intellectual capital while return on equity and return on assets was proxies for financial performance. Sample sizes of fifty (50) out of a population of eighty (80) listed non-financial firms on Nigerian Stock Exchange as at December 2018 were purposively selected for the study. Data collected were analyzed using descriptive statistics and panel regression analysis. The results of the study revealed that human capital efficiency, capital employed efficiency, firm size had significant positive effect on return on equity while human capital efficiency, structural capital efficiency, capital employed efficiency and leverage had a significant effect on return on assets. The study concluded that intellectual capital has positive significant effect on financial performance measures. The study recommended a policy framework for the management to increase intellectual capital utilization through investment in human and customer capital to enhance their financial performance and maintain competitive edge.